Elemental Composition Analysis in Water From Galas River, Kelantan - Tuan Ahmad, Tuan Safhwan (2016)
The study was undertaken to assess the Water Quality Status and analyze the selected metals in water from the rural areas. This study focused on analysis of two different seasons namely Normal Season (July) and Hazy Season (September) in river. The Sungai Galas catchment at Dabong, Kelantan was used as a case study. The total catchment area of Sungai Galas is 15km. A total of 10 water samples were collected for each season from the river. All the samples were analyzed for the ten elements of metals namely Cadmium, Tin, Barium, Manganese, Ferum, Calcium, Silver, Natrium, Lead, and Copper using standard procedures and the results were compared with Ministry of Health (MOH) Malaysia guideline values. Important parameters such as such as Temperature (°C), Conductivity (mS/cm), Velocity (m/s), Turbidity (NTU), Salinity (ppt) and Dissolved Oxygen (DO) and pH were recorded in order to identify water quality status in Galas River. The level of metals was determined by using X-Ray Fluorescence (XRF) analysis. Therefore, the results of the present study have shown the range concentration of all metals values during normal season states the range value of Cd (0-15 mg/L), Sn (12-26 mg/L), Ba (0-33 mg/L), Mn (0 mg/L), Fe (0-170 mg/L), Ca (0-292 mg/L), Ag (0-3 mg/L), Na (0-11700 mg/L) Pb (0) and Cu (0 mg/L). Meanwhile hazy season states the range value of Cd (0-86 mg/L), Sn (11-106 mg/L), Ba (9-462 mg/L), Mn (0-121 mg/L), Fe (0-8380 mg/L), Ca (0-1400mg/L), Ag (0-79 mg/L), Na (0-21700 mg/L) Pb (0) and Cu (0-74 mg/L). All of the results of metals were above the MOH recommended maximum admissible limits.